Nucleolar origins: challenging perspectives on evolution and function - Israel Muñoz-Velasco; Ana Karen Herrera-Escamilla; Alberto Vázquez-Salazar (Open Biology, 2025)
The nucleolus, once considered a mere ‘ribosome factory’, is now recognized as a dynamic hub influencing nearly every aspect of cellular life, from genome organization to stress response and ageing. Despite being a hallmark of eukaryotic cells, recent discoveries reveal that even prokaryotes exhibit nucleolus-like structures, hinting at ancient origins for nucleolar functions. This review explores the evolutionary journey of the nucleolus, tracing its roots back to early life and examining its structural and functional diversity across domains. We highlight key nucleolar proteins that play vital roles not only in ribosome production but also in regulating cell cycle, DNA repair and cellular stress, linking nucleolar activity directly to health and disease. Dysfunctions in nucleolar processes are implicated in cancer, ribosomopathies and neurodegenerative disorders, positioning the nucleolus as a critical target for innovative therapeutic strategies. As advanced imaging and molecular techniques unlock deeper insights into both canonical and mysterious non-canonical roles, the nucleolus stands as a model for how cellular microenvironments can evolve to meet complex biological demands. By addressing open questions surrounding the evolution of the nucleolus, its organization and diverse functions, the ideas presented here aim to contribute to the ongoing discussion, challenging traditional paradigms and suggesting new avenues for uncovering the fundamental principles that drive cellular life.